Intelligent Technologies for Interactive Entertainment 6th International Conference, INTETAIN 2014, Chicago, IL, USA, July 9-11, 2014. Proceedings - Reidsma, Dennis; Choi, Insook; Bargar, Robin (Springer eBooks, 2014)
This book constitutes the proceedings of the 6th International Conference on Intelligent Technologies for Interactive Entertainment, INTETAIN 2014. The 8 full papers presented together with 4 special session papers, 4 panels, and 6 extended abstracts were carefully selected from 26 submissions. The papers present interdisciplinary research, covering topics such as creativity applied to technology, AI, cognition, and models of engagement and play. The special session papers address the topic of humor in intelligent environments.